2004
DOI: 10.1111/j.1774-9987.2004.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

2004 Japanese Society for Dialysis Therapy Guidelines for Renal Anemia in Chronic Hemodialysis Patients*

Abstract: The guideline committee of Japanese Society for Dialysis Therapy (JSDT), chaired by Professor F. Gejyo of Niigata University, now publishes an original Japanese guideline entitled 'Guidelines for Renal Anemia in Chronic Hemodialysis Patients'. It includes the re-evaluation of the usage of recombinant human erythropoietin (rHuEPO) with the medical and economical arguments regarding the prognosis and the quality of life of Japanese hemodialysis patients. This guideline consists of 7 sections. The first section c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 72 publications
(50 reference statements)
0
59
3
1
Order By: Relevance
“…8 As compared with Hct, Hgb is seen to be a better measure to use to monitor and manage anemia in patients with chronic kidney disease. 9,10 The JSDT 2004 Guideline briefl y reported that Hct levels on Mondays (the beginning day of the dialysis week) were considered to be corresponded to 99.1% of those on Wednesdays (the middle day of the dialysis week). 7 Results from the present study also demonstrated that Hct levels at the beginning day of the dialysis week were corresponded to 96.9% of those at mid-dialysis week.…”
Section: Discussionmentioning
confidence: 99%
“…8 As compared with Hct, Hgb is seen to be a better measure to use to monitor and manage anemia in patients with chronic kidney disease. 9,10 The JSDT 2004 Guideline briefl y reported that Hct levels on Mondays (the beginning day of the dialysis week) were considered to be corresponded to 99.1% of those on Wednesdays (the middle day of the dialysis week). 7 Results from the present study also demonstrated that Hct levels at the beginning day of the dialysis week were corresponded to 96.9% of those at mid-dialysis week.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anaemia, defined as a haemoglobin concentration <120 g/l in women and <130 g/l in men (a sex-specific definition established by the WHO [22]), was observed in 19 (12.8%) women and 32 (10.2%) men. Using the sexand age-specific anaemia criteria in Japanese adults proposed by the Japanese Society for Dialysis Therapy Guidelines [23], only 6 (4.0%) women and 12 (3.8%) men were diagnosed as having anaemia. Based on ADAguideline criteria [18], 126 (84.6%) women and 252 (80.0%) men were classified as having normoalbuminuria, and 23 (15.4%) women and 63 (20.0%) men were classified as having microalbuminuria; 26 (17.4%) [24].…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…However, the Japanese Society for Dialysis Therapy (JSDT) published anemia management guidelines in 2004 that recommended an Hb target level of 10-11 g/dl for most patients and 11-12 g/dl for younger, more active patients. 27 A 2008 update to the JSDT guidelines added 12 g/dl as a criterion for reducing or interrupting ESA treatment. 28 Although the distribution of lower Hb targets reported by Japanese DOPPS facilities has not changed much since 2010 ( Figure 3B), in recent years, we have observed a higher proportion of Japanese DOPPS facilities reporting upper Hb targets of 12 g/dl ( Figure 3A).…”
Section: Anemia Treatment Targets: 2010-2013mentioning
confidence: 99%